Studi Perbandingan Routing Protocol Open Shortest Path First (OSPF) dan Enhanced Interior Gateway Routing Protocol (EIGRP) pada IPv6 dengan Menggunakan Simulator Graphical Network Simulator 3 (GNS3) - Kelvin Thesman; Agustinus Noertjahyana; Resmana Lim (Jurnal Infra, 2017)
Since the development of computer networks, humans no longer have to implement computer networks in real conditions but can be implemented through network simulators. One of them is GNS3 (Graphical Network Simulator 3). Due to this development, IPv4 stocks have reached their limits and will be replaced with IPv6. Various routing protocols are available to support IPv6. The routing protocols are OSPF (Open Shortest Path First) and EIGRP (Enhanced Interior Gateway Routing Protocol). OSPF and EIGRP have many differences in the algorithm used, so in this study will be analysed the comparison of both routing protocol in IPv6 implementation. In this study, will be designed a computer network and tested. Testing is done by using ping and trace route. In addition, there is also testing for convergence time.The results show that the value of delay and throughput of OSPF is better 2-15% than EIGRP on the condition of the connection is not down. On the other hand, when the connection was down, EIGRP is better 45-52% for delay and 38-48% for throughput. Both have the same value for packet loss during normal connection and EIGRP is better 11-16% when connection down. In addition, EIGRP has an initial convergence time of 8 seconds, while OSPF is within 19 seconds. Moreover, EIGRP has convergence time while adding links with a time of 2-6 seconds and OSPF with a time of 8-10 seconds.